Phytochemicals and biological properties of Annona coriacea Mart. (Annonaceae): A systematic review from 1971 to 2020 - Rocha, Giovanna Nogueira da Silva Avelino Oliveira; Dutra, Lívia Macedo; Lorenzo, Vitor Prates; Almeida, Jackson Roberto Guedes da Silva (Chemico-biological interactions, 2021)
Annona coriacea Mart., popularly known as “marolo”, “araticum” and “araticum-liso” is a species distributed in Paraguay and Brazil, and easily found in Caatinga, Cerrado, and Pantanal biomes. The araticum has been used in folk medicine to treat stomatitis, neuralgia, rheumatism, headaches, furuncle, ulcers, and dermatitis. This systematic review aimed to provide a comprehensive overview of the ethnomedicinal use, phytochemistry, and pharmacological activity of A. coriacea. A search for scientific articles of electronic databases (Science Direct, PubMed, Lilacs, Scopus, Google Scholar, Scielo, and Web of Science) was performed identifying studies published until November 2020. All papers considering traditional medicinal uses, phytochemistry, and pharmacological properties were included. Forty-six articles (n = 212 subjects) met the inclusion criteria set for this review. Of the 46 articles reviewed, 34 were focused on biological activity investigations, while 12 were limited to phytochemical studies. These studies showed the presence of a diversity of secondary metabolites such as acetogenins, sesquiterpenes, alkaloids, flavonoids, and diterpenes. To date, pharmacological tests have demonstrated significant biological activities of this plant, being the most promising anticancer, anti-inflammatory, antiulcer, and insecticide activities. Additionally, the medicinal utilization of A. coriacea appears to be promising, supporting its possible uses for human health with antioxidant, anxiolytic, antiulcer, insecticide, and antiparasitic activities. Ultimately, comprehensive studies involving clinical trials are required to validate the existing traditional practices and their related health benefits scientifically. •The ethnobotany records several medicinal properties of leaves, seeds and roots of Annona coriacea.•Phytochemical constitution of A. coriacea is little explored.•Several bioactivities reported, including anticancer and anti-inflammatory.•Clinical trial studies have not yet been reported.